Seasonal movements and ecological markers as evidence for migration of common minke whales photo-identified in the eastern North Pacific - Towers, Jared R.; McMillan, Christie J.; Malleson, Mark; Hildering, Jackie; Ford, John K. B.; Ellis , Graeme M. (J. Cetacean Res. Manage., 2023)
In the eastern North Pacific Ocean, common minke whales (Balaenoptera acutorostrata) are widespread but encountered relatively infrequently. It is generally believed that they make annual migrations between higher latitudes in the summer and lower latitudes in the winter; however, in some temperate coastal regions where common minke whales have been sighted year-round they have been referred to as resident. To determine movement patterns of common minke whales found in coastal waters of British Columbia and Washington we examined photo-identification data that were collected opportunistically from 2005–12. These data were from four non-overlapping areas between 48°N and 53°N. Despite year-round search efforts, common minke whales were only encountered between April and October. Most of the 44 unique individuals identified in 405 encounters displayed fidelity to areas both within and among years. Five of these whales made relatively large-scale intra-annual movements between areas on six occasions. They were documented to move up to 424km in a northerly direction in spring and up to 398km in a southerly direction in autumn. The seasonal patterns of these movements provide new insights into the foraging ranges and migrations of the individuals. Ecological markers provide evidence that the common minke whales photographed undertake annual long distance migrations. Scars believed to be from cookiecutter shark (Isistius brasiliensis) bites were observed on 43 individuals and the majority of whales documented with good quality images each year had acquired new scars since the previous year. Furthermore, the commensal barnacle Xenobalanus globicipitis was observed on three individuals. Since these sharks and barnacles are from relatively warm waters, it can be inferred that they interacted with the common minke whales at lower latitudes. These findings may have important implications for the definition and management of common minke whale stocks and/or populations in the eastern North Pacific.